Gestión financiera en la Federación Deportiva Provincial Estudiantil de Los Ríos (FEDESRÍOS) periodo 2022 y 2023. - Toaza Candel, Cesar Alayn (2024)
The case study focuses on the Provincial Student Sports Federation of Los Ríos (FedesRíos), which is located in the city of Babahoyo, on Isaías Chopitea and García Moreno streets, which is facing liquidity problems due to poor financial management and, Furthermore, as it belongs to the public sector, the budget allocation does not arrive on established dates, which is why its financial and operational stability is at risk. The research aims to identify the factors that intervene in its profitability, analyze and evaluate its financial situation using analysis tools and financial indicators. The methodologies used include the collection of information through an owner interview, financial analysis and the use of financial indicators to evaluate the financial situation and performance. The results showed that the company does not have liquidity because its current assets cannot cover its current liabilities, its level of debt is very high because it depends on liabilities to be able to finance its activities and despite obtaining an improvement in its profit. . operating is not enough to overcome its liquidity and debt problems. Strategies were proposed to recover the liquidity of the Provincial Student Sports Federation of Los Ríos (FedesRíos). Among these, it is considered important to search for additional sources to be able to finance ourselves in the short term, look for less expensive and long-term financing options; This would help alleviate short-term debt pressure, plus they should consider diversifying their income sources.